Penggunaan Persamaan kolinier Untuk rektifikasi Citra Satelit Spot Secara Parsial - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
Commonly, to obtain object position in a map coordinate system, satellite images have to be transformed into orthoimage and then do vectorization. This method encompasses two stages, i. e. transforming raster into raster image and then transforming raster into vector data. In photogrammetry, there is a method for determining object's horizontal position on a map coordinate system from a single aerial photograph/image using a collinear equation. By this method, object' horizontal position on image can be determined in map coordinate system directly and also involves variation of earth surface. Semarang area, which covered by a full scene of SPOT Panchromatic image, was taken as a research area. Application of collinear equation in research area is done partially, i.e. dividing the area, which has size of 30 km x 30 km, into a experiment areas. The research shows, 2 areas and 4 areas fulfill specification of BAKOSURTANAL's topographic map at 1:50.000 and 1:100.000 scale. The two areas have size 5,7 x 3,2 km2 and 8,0 x 4,2 km2, with flat terrain, and identification of Ground Control Points and Check Points on SPOT image can be done clearly.